Clinical evaluation of rare copy number variations identified by chromosomal microarray in a Hungarian neurodevelopmental disorder patient cohort - Anna Lengyel; Éva Pinti; Henriett Pikó; Árvai Kristóf; Tünde Abonyi; Zaránd Némethi; György Fekete; Irén Haltrich (Molecular Cytogenetics, 2022)
Abstract Background Neurodevelopmental disorders are genetically heterogeneous pediatric conditions. The first tier diagnostic method for uncovering copy number variations (CNVs), one of the most common genetic etiologies in affected individuals, is chromosomal microarray (CMA). However, this methodology is not yet a routine molecular cytogenetic test in many parts of the world, including Hungary. Here we report clinical and genetic data of the first, relatively large Hungarian cohort of patients whose genetic testing included CMA. Methods Clinical data were retrospectively collected for 78 children who were analyzed using various CMA platforms. Phenotypes of patients with disease-causing variants were compared to patients with negative results using the chi squared/Fisher exact tests. Results A total of 30 pathogenic CNVs were identified in 29 patients (37.2%). Postnatal growth delay (p = 0.05564), pectus excavatum (p = 0.07484), brain imaging abnormalities (p = 0.07848), global developmental delay (p = 0.08070) and macrocephaly (p = 0.08919) were more likely to be associated with disease-causing CNVs. Conclusion Our results allow phenotypic expansion of 14q11.2 microdeletions encompassing SUPT16H and CHD8 genes. Variants of unknown significance (n = 24) were found in 17 patients. We provide detailed phenotypic and genetic data of these individuals to facilitate future classification efforts, and spotlight two patients with potentially pathogenic alterations. Our results contribute to unraveling the diagnostic value of rare CNVs.